Judging criteria in international professional surfing championships. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p439 - Saray Giovana dos Santos; Rosemeri Peirão (Universidade Federal de Santa Catarina, 2012)
DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n4p439This study investigated the association between judges' scores and the variables that represent judging criteria of surfing events. A total of 164 waves ridden by 21 international surfers were recorded and analyzed in two stages of the Brazilian ASP World Tour (2007 and 2010). The following tests were used for descriptive analysis of data: the Kolmogorov-Smirnov and the Student t test, one-way ANOVA, the Tukey post-hoc test and Pearson correlation analysis (p≤0.05). Significant differences were found between the scores of waves with bad, average and exceptional take-offs (p≤0.05) and with controlled exit, fall in the main section of the wave (MSW) and after the MSW (p≤0.001). There was a significant correlation (p≤0.05) between wave scores and the following variables: frequency of imbalance in the maneuvers (r=-0.30), percentage of maneuvers in the critical section of the wave (r=0.68), variety of maneuvers (r=0.62), frequency of carving (r=0.51), re-entry (r=0.43), floater (r=0.23) and cut-back (r=0.27) maneuvers, length of ride (r=0.76) and total frequency of maneuvers (r=0.79) for the ASP World Tour 2007; percentage of maneuvers in the critical section of the wave (r=0.34), variety of maneuvers (r=0.70), frequency of carving (r=0.46), re-entry (r=0.51), cut-back (r=0.30) and aerial maneuvers (r=0.30), length of ride (r=0.71) and total frequency of maneuvers (r=0.75) for the ASP World Tour 2010. The results showed that all surfing criteria used by judges in this study correlated significantly with scores in the ASP World Tour 2007 and 2010, except for frequency of imbalances in the second competition.